Comparison of shear bond strength of two different adhesive systems: an in vitro study - Rosangela Maurina; Cristiane Giacomini; Fernanda Tomazoni; Mariá Cortina Bellan; Rodrigo Alessandretti; Daniel Galafassi (Faculdade Meridional IMED, 2019)
Objectives: The present study aimed to evaluate the shear bond strength of two adhesive systems applied in different amounts of enamel and bovine dentin layers. Methods: The factors studied were adhesive systems at two levels: Single Bond Universal and Single Bond 2. The experimental samples were composed of 30 bovine enamel fragments (n = 5) and 30 bovine dentin fragments (n = 5) randomly divided into two experimental groups of enamel and two groups of dentin, subdivided into 3 different application modes adhesive system in 1, 2 or 3 layers. Results: The Single Bond 2 and Universal Bond adhesives, when applied in one or three layers in to the dentin or enamel, presented statistical similarity (p=0.8726). When comparing the Single Bond 2 and Single Bond Universal adhesive system in the dentin substrate, the application of two layers of the adhesive system implies an increase in the statistically significant adhesive resistance (p=0,000) for the Universal Single Bond group applied to dentin. Conclusion: The Single Bond Universal adhesive presented a higher adhesive strength than Single Bond 2 adhesive when applied in two layers on dentin substrate. For the enamel substrate, both adhesive systems are effective regardless of the number of layers applied.